From the fat body to the hemolymph: Profiling tick immune and storage proteins through transcriptomics and proteomics - Urbanová, Veronika; Lu, Stephen; Kalinová, Eliška; Martins, Larissa; Kozelková, Tereza; Dyčka, Filip; Ribeiro, José M; Hajdušek, Ondřej; Perner, Jan; Kopáček, Petr (Insect biochemistry and molecular biology, 2024)
Ticks are blood-feeding arachnids that are known to transmit various pathogenic microorganisms to their hosts. During blood feeding, ticks activate their metabolism and immune system to efficiently utilise nutrients from the host's blood and complete the feeding process. In contrast to insects, in which the fat body is known to be a central organ that controls essential metabolic processes and immune defense mechanisms, the function of the fat body in tick physiology is still relatively unexplored. To fill this gap, we sought to uncover the repertoire of genes expressed in the fat body associated with trachea (FB/Tr) by analyzing the transcriptome of individual, partially fed (previtellogenic) Ixodes ricinus females. The resulting catalog of individual mRNA sequences reveals a broad repertoire of transcripts encoding proteins involved in nutrient storage and distribution, as well as components of the tick immune system. To gain a detailed insight into the secretory products of FB/Tr specifically involved in inter-tissue transport and humoral immunity, the transcriptomic data were complemented with the proteome of soluble proteins in the hemolymph of partially fed female ticks. Among these proteins, the hemolipoglyco-carrier proteins were predominant. When comparing immune peptides and proteins from the fat body with those produced by hemocytes, we found that the fat body serves as a unique producer of certain immune components. Finally, time-resolved transcriptional regulation of selected immune transcripts from the FB/Tr was examined in response to experimental challenges with model microbes and analyzed by RT-qPCR. Overall, our data show that the fat body of ticks, similar to insects, is an important metabolic tissue that also plays a remarkable role in immune defense against invading microbes. These findings improve our understanding of tick biology and its impact on the transmission of tick-borne pathogens.
Keywords: Ixodes; Gene Expression Profiling; proteomika; hemolymfa; tukové těleso; klíště; Animals; Female; Hemolymph; ženské pohlaví; Proteomics; Fat Body; proteiny členovců; stanovení celkové genové exprese; Arthropod Proteins; zvířata